General education teachers' math instructional practices in kindergarten classrooms with and without students with emotional and behavioral disabilities. (January 2019) - Gottfried, Michael A.; Kirksey, J. Jacob
Abstract: Including students with disabilities in general education classrooms is a priority nationwide, but little is known whether classroom compositions have implications for frequencies of classroom activities. This study focuses on kindergarten classrooms that do and do not have students with emotional and behavioral disabilities (EBDs). Using national data, we found teachers reported greater frequency of traditional math activities if they had students with EBDs in their classroom. Teachers in classrooms with students with EBDs reported more frequencies of math content that involved advanced practical and writing skills. Differences in findings arose based on teacher qualifications. Implications for policy are discussed. Highlights: Teachers with students with emotional or behavioral disabilities reported using more traditional practices. Teachers also reported teaching more math content that used writing skills. Differences in types and frequencies of mathematics instruction arose based on teacher qualifications.